TURKISH-TO-ENGLISH SHORT STORY TRANSLATION BY DEEPL: HUMAN EVALUATION BY TRAINEES AND TRANSLATION PROFESSIONALS VS. AUTOMATIC EVALUATION - Halise Gülmüş Sırkıntı (English Studies at NBU, 2025)
This mixed-methods study aims to evaluate the quality of Turkish-to-English literary machine translation by DeepL, incorporating both human and automatic evaluation metrics while engaging translation trainees and professional translators. Raw MT output of two short stories, Mendil Altında and Kabak Çekirdekçi, evaluated by both groups via TAUS DQF tool and evaluators wrote reports on the detected errors. Additionally, BLEU was employed for automatic evaluation. The results indicate a consensus between trainees and professionals in assessing MT accuracy and fluency. Accuracy rates were 80.59% and 80.50% for Mendil Altında, and 73.08% and 82.35% for Kabak Çekirdekçi. Fluency rates were similarly close, 71.96% and 72.32% for Mendil Altında, and 66.81% and 62.09% for Kabak Çekirdekçi. Bleu scores, particularly 1-gram results, align with the human evaluators' results. Furthermore, reports show that trainees provided more detailed analysis, frequently using meta-language, suggesting that increased exposure to metrics enhances trainees' ability to identify fine-grained MT errors.